2009
DOI: 10.1038/onc.2009.205
|View full text |Cite
|
Sign up to set email alerts
|

The role of SPARC in the TRAMP model of prostate carcinogenesis and progression

Abstract: SPARC (Secreted Protein Acidic and Rich in Cysteine), is a matricellular glycoprotein that is produced by tumor and/or neighboring stroma. In human prostate cancer, SPARC immunoreactivity is highest in metastatic lesions but distinct contributions of tumoral and stromal SPARC to tumorigenesis and progression are unclear. To determine the role of SPARC in primary prostate tumorigenesis, we crossed SPARC-null (SP À/À ) with TRAMP (Transgenic Adenocarcinoma of Mouse Prostate) mice.mice exhibited accelerated cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 55 publications
0
72
0
Order By: Relevance
“…Moreover, the controversy of the pathological role of SPARC in prostate cancer was further affirmed in two separate studies that utilized the SPARC knockout and transgenic adenocarcinoma of the mouse prostate (TRAMP) mouse models. Although Said et al (25) found an inhibitory role of SPARC in tumor and metastatic growth, another study did not identify any role of SPARC in tumor progression and metastasis (49). The discrepancy in the pathological outcome evident in these studies might be due to the differences in genetic background of the mice used in the study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the controversy of the pathological role of SPARC in prostate cancer was further affirmed in two separate studies that utilized the SPARC knockout and transgenic adenocarcinoma of the mouse prostate (TRAMP) mouse models. Although Said et al (25) found an inhibitory role of SPARC in tumor and metastatic growth, another study did not identify any role of SPARC in tumor progression and metastasis (49). The discrepancy in the pathological outcome evident in these studies might be due to the differences in genetic background of the mice used in the study.…”
Section: Discussionmentioning
confidence: 90%
“…SPARC plays a significant role in tissue remodeling, maintaining cell matrix integrity and interaction and collagen fiber assembly (34). Stroma-as well as tumor-secreted SPARC is known to affect tumor growth in cell type-and context-dependent manners by regu- lating cell proliferation, adhesion, migration, invasion, and angiogenesis (25,(35)(36)(37)(38). In prostate cancer, apparent conflicting results regarding SPARC expression in both clinical and experimental studies suggest that the role of SPARC is even more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Use of SPARC knockout (Sparc -/-) mice revealed that SPARC suppresses syngeneic and oncogenedriven tumors (9,(11)(12)(13)(14) through regulation of matrix deposition and through antiinflammatory, antiangiogenic, antiproliferative, and proapoptotic effects, while SPARC has been found to be upregulated in the stroma (9,15). SPARC exerts autocrine and paracrine inhibition of cancer cell proliferation through cell-cycle arrest (8,9,13,16,17) and suppression of survival signaling (7,11,12,18,19), cancer cell adhesion, and invasion (8,11,12,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms through which Sparcl1 regulates cellular adhesion and migration are not well understood; however, Sparcl1 has been shown to bind type I collagen, a component of the extracellular matrix that potentiates tumor cell migration and invasion (11)(12)(13). Although the C-terminal domain of SPARCL1 is highly homologous to SPARC, an inhibitor of prostate tumorigenesis and progression (14), the relationship of SPARCL1 itself to prostate cancer aggressiveness has not been well characterized.…”
mentioning
confidence: 99%